The Effect of Work Stress and Satisfaction of Collector Performance in PT Federal International Finance Singaraja Branch Office - Krisna Heryanda, Komang (International Journal of Social Science and Business, 2019)
This study aimed at determining the effect of (1) job stress and job satisfaction toward collector's performance, (2) job stress toward collector's job satisfaction, (3) job stress toward collector's performance, and (4) job satisfaction toward collector's performance at PT. Federal International Finance Singaraja Branch Office. The design of this study was causal quantitative. The populations of this study were 40 people. Data were collected by questionnaire, and analyzed by path analysis. The results showed that: (1) job stress and job satisfaction had significant effect toward collector's performance (2) job stress had a negative and significant effect toward collector job satisfaction, (3) job stress had a negative and significant effect toward collector's performance, and (4) job satisfaction had a positive and significant effect toward collector's performance at PT. Federal International Finance in Singaraja